THE ENGINEERING AND TECHNICAL EDUCATIONAL CONTENT WITHIN THE CONTEXT OF ENSURING THE COMPETITIVENESS OF GRADUATES (Socio-economic relations in the digital society, 2019)
In the article the results of analysis of scientifi c approaches to improve the university graduates’ competitiveness are presented and key principles of designing engineering education’s content, that take into account the current realities and perspectives of development of the domestic industry towards its adaptation to market conditions and the global informatization process, are defined. It is found that among the scientifi c approaches to search ways of increasing competitiveness of graduates. The first group is based on recognition of current requirements of employers as benchmarks to formulate professional training tasks. The second group is based on the metrology understanding of definition of «competitiveness» and on the recognizing the forming an economic consciousness as an important component of professional training. It is proved that search for ways to solve problems of increasing the competitiveness of future engineers in the job market should be conducted based on recognition of economic nature of competition in the job market and taking into account the socio-economical transformations in the industrial sector as a result of the global informatization process. It is shown that under current conditions in the design of content of engineering education the economic properties of technical objects and systems (generalized objects of future professional activity of students of engineering  specialties) and the laws and regularities, by which they undergo an evolution, are should be taken into account.
Keywords: competitiveness; job market; the content of engineering education; market economy; informatization